STRATEGI PEMASARAN PERSFEKTIF ETIKA BISNIS ISLAM - Vandita, Lalu Yoga (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
This study aims to find out how the strategies applied by rattan woven entrepreneurs in Monggaas Village, Kopang District, Central Lombok. The type of research used is the type of qualitative research. Data collection techniques using observation, interviews, and documentation. The data analysis used includes three stages, namely data reduction, data presentation and verification/conclusion. The result of this research is that the marketing strategy carried out by the community is in accordance with Islamic business ethics, namely by being honest, selling good quality goods, not using oaths, being generous, and setting prices fairly. The marketing strategy implemented by the people of Monggas Village is simply, sending products to stockists who have spread throughout Indonesia and using the internet to market their products.